Recent advances in solid‐state metal–air batteries. Issue 2 (9th November 2022) - Sun, Qi; Dai, Lei; Luo, Tingting; Wang, Ling; Liang, Feng; Liu, Shan
Abstract: Solid‐state metal–air batteries have emerged as a research hotspot due to their high energy density and high safety. Moreover, side reactions caused by infiltrated gases (O2, H2 O, or CO2 ) and safety issues caused by liquid electrolyte leakage will be eliminated radically. However, the solid‐state metal–air battery is still in its infancy, and many thorny problems still need to be solved, such as the large resistance of the metal/electrolyte interface and catalyst design. This review will summarize some important progress and key issues for solid‐state metal–air batteries, especially the lithium‐, sodium‐, and zinc‐based metal–air batteries, clarify some core issues, and forecast the future direction of the solid‐state metal–air batteries. Abstract : Research on solid‐state metal–air batteries has made great progress in the development of clean and renewable electrochemical energy storage devices. In this review, some important progress and key issues of solid‐state metal–air batteries are summarized. This review provides valuable insights into the development of solid‐state metal–air batteries and forecasts the future direction of the solid‐state metal–air batteries.